MEMBANGUN KETAHANAN MENTAL ANAK DARI KELUARGA BROKEN HOME: Integrasi Maqashid Syariah dan Teori Ekologi Sistem Bronfenbrenner - Hamdi, Muhammad; Sugitanata, Arif; Hamroni, Hamroni (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2023)
Abstract This study aims to investigate the development of mental resilience in children from broken homes. Particular focus is given to efforts to build their mental resilience in the face of the stress, instability and emotional challenges of such family dynamics. This study employs qualitative research through desk research to integrate two primary theoretical frameworks: Maqashid Sharia and Bronfenbrenner's Ecological Systems Theory. The results show that building children's mental resilience requires a holistic approach involving a safe and supportive environment, mental health education, therapy, and community and school involvement. Education and training for parents and caregivers are also essential to correct behaviours that can negatively impact children's mental health. Through the lens of Maqashid Sharia and Bronfenbrenner's Systems Ecology theory, this research offers new insights into a comprehensive approach to supporting children from broken homes, demonstrating the importance of inter-systems cooperation to support children's long-term mental well-being and resilience.